Hot tub time machine [videorecording (DVD)] - Cusack, John, 1966-; Corddry, Rob; Robinson, Craig, 1971-; Duke, Clark, 1985-; Glover, Crispin; Caplan, Lizzy, 1982-; Chase, Chevy (MPI Media Group, 2025)
When a group of middle-aged men travel to a ski resort seeking a temporary escape from their failed, miserable lives, a drunken accident in a hot tub sends them back to 1986, where they get a chance to relive a night from the past and possibly change their futures forever.